Microscopic observation of a root-adhering factor Avin_16040 in Azotobacter vinelandii and Escherichia coli during association with rice root - Liew, Pauline Woan Ying; Jong, Bor Chyan; Najimudin Nazalan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Microbial adherence to plant root is the initial step in a beneficial plant-microbe interaction. Quantitative RT-PCR analysis deduced the Avin_16040 gene showed upregulated expression when Azotobacter vinelandii was adhered to the rice root. By transforming the full-length Avin_16040 gene into a heterologous host Escherichia coli, the recombinant clones displayed filamentous cell shapes in contrast to the rod-shape of wild type cells. Besides full-length gene insert, some E. coli clones were detected to contain truncated Avin_16040 gene inserts but still shape-shifted to filamentous cells. Further analysis by DNA sequencing revealed the shape-shifting E. coli clones contained 3’-end truncated Avin_16040 gene, while E. coli clones containing the 5’-end truncated Avin_16040 gene remained rod-shaped. The cell surface topographies of A. vinelandii and E. coli cells in the presence and absence of Avin_16040 gene and in association with rice root adherence were analysed using atomic force microscopy.